DEVELOPMENT OF MAINTENANCE AND STRUCTURE OF REGIONAL EDUCATION IS AT BASIC AND SENIOR SCHOOL OF UKRAINE (1991-2010) - Bugrii, Volodymyr S. (Educological discourse, 2014)
In the article changes are analysed in maintenance and structure of regional education at basic and senior school of Ukraine in a period from 1991 to 2010 it is Set that cardinal to the table of contents changes in the system of education began after proclamation of independence of Ukraine. They stipulated actualization of study of a particular region, that found the embodiment in further expansion of educational space, where the use of local material was foreseen. Yes, in the project of the program from history of Ukraine for 7-11 classes (in 1992) independent regional lessons were stored «Our edge». In the same time, their division into periods and placing some changed for to the classes. To the increase of amount of regional material in the programs objectively substituting of school course of history of the USSR promoted by the course of history of Ukraine. In the programs from biology 90th of study of the vegetable and animal world continued to be built on regional basis. The certificate of it was that the choice of objects for a study contacted with the specific of agricultural production of concrete locality. The excursions foreseen by the program acquainted students with many-sided nature of plants and animals of native edge, copulas between them and factors of lifeless nature. Practical works from biology it was continued to carry regional aspiration, as executed on local material. In offered by Department of education of Ukraine on 1995-1996 school year three variants of the programs from Ukrainian literature scalene regional work assignments were foreseen. It could be deeper working of work of writers-countrymen that was studied in accordance with the program, or acquaintances with writers, works of that do not enter to the programs, but life and work their related to certain locality. A teacher could acquaint students with work of modern local literati-beginners. At the beginning of 2000th substantial changes took place in the regional constituent of the school programs of basic and senior school. They were conditioned by Decree of President of Ukraine № 35/2001 from January, 23, 2001 «About measures in relation to support of regional motion in Ukraine». In this document specified on a necessity to provide development and including to the curricula and programs of general, out-of-school, and higher educational establishments of themes from the study of a particular region taking into account the specific of regions of Ukraine. In addition, the protracted development of state standards of general preparation of students after that maintenance of educational industries had to be built on national basis. On such conditions in the program from history in a release in 2001 the chronologic-successive construction of lessons was picked up thread «Our edge». Unchanging it remained and conceptual vision of task of study of a particular region in the course of geography of Ukraine is must provide the idea of students about the region, as component part of the state. In the program from biology of 2001 р. regional material came forward in quality of evident SE for the best realization of intercommunication of structure and functions of living organisms. He provided forming of ideas about an organism as integral system. Program from Ukrainian literature in 2001, as well as previous, took into account a requirement in the acquaintance of schoolchildren with history and culture of native edge by means of artistic word. In her the requirements of the obligatory use of regional material were stopped up on the lessons of literature. The duty changing in maintenance and structure of study of a particular region in the school programs were related to passing to the programs for 12-years-old school. The program worked out for 12-years-old school from history in 2005 contained certain innovations that had to strengthen the value of study of a particular region. In the program from geography attention to the study of native edge went down substantially. Due to the exception of regional material original programmers tried to decrease the overload of students, related to working of plenty of information. In the school program from Biology in 2005 the study of a particular region was confessed to one of components of maintenance of object in quality of the real objects and processes of wild-life. Looking after and opening them on your own students joined in activity, that had on an aim research of structure, properties, intercommunications. The program from Ukrainian literature in 2005 kept a previous structure. In every class the themes of lessons sneaked up «Literature of native edge» or after genres, or after chronologic periods.